Consumption 3.0: A web-based proposal for supporting social and ecological awareness in private consumption - Petring, Alexander (Momentum Quarterly, 2013)
Given the increasing environmental challenges, and increasing social problems in many countries around the world, a debate started about the pros and cons of involving private consumption in solving the sustainability problem. Building on this debate, the article sketches out a web-based proposal for strengthening social and ecological aspects in private purchasing decisions.